2020
DOI: 10.1186/s12301-020-00056-3
|View full text |Cite
|
Sign up to set email alerts
|

Modified R.E.N.A.L nephrometry score for predicting the outcome following partial nephrectomy

Abstract: Background It was difficult to compare the outcome of partial nephrectomy among different studies due to the absence of standardized description of different renal masses. This problem led to the development of nephrometry scoring systems. R.E.N.A.L. is among the commonest nephrometry scoring systems; however, some studies failed to find any relation between R.E.N.A.L. with perioperative outcome. We evaluated our designed newly modified nephrometry score in prediction of outcome following partial nephrectomy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… 29 , 31 A recent study by Salah M and co-workers indicated that a newly modified nephelometry score (MNS) was associated with better prediction of the outcome of partial nephrectomy when compared to R.E.N.A.L. 32 In future studies, the data will try to be further compared by using the newly modified nephelometry score.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 31 A recent study by Salah M and co-workers indicated that a newly modified nephelometry score (MNS) was associated with better prediction of the outcome of partial nephrectomy when compared to R.E.N.A.L. 32 In future studies, the data will try to be further compared by using the newly modified nephelometry score.…”
Section: Discussionmentioning
confidence: 99%
“…N.A.L. 25 Some other studies already suggest using simplified scores. Desantis et al suggest that a score incorporating tumour size and some measure of the tumour's depth/contact with the renal parenchyma can likely perform at least as well as RENAL or PADUA systems.…”
Section: Dovepressmentioning
confidence: 99%
“…[ 13 ] With regards to OPN surgery, Salah et al reported good renal function after OPN using brief warm ischemia or zero-ischemia. [ 14 ] In contrast, cold renal ischemia in OPN was considered to be acceptable for up to 2 hours. Nevertheless, it is preferable to keep cold ischemia time as short as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Salah et al showed the relationship between the original NS and a modified NS for OPN. [ 14 ] They described the newly modified NS was better at predicting outcomes in OPN patients. In our series, we used both the original NS and modified NS, and showed risk factors for impaired renal function after OPN using both nephrometry models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation